Classroom-Based Assessment Practices during the COVID-19 Outbreak in Indonesia: EFL Students’ Perceptions and Challenges - Farida Nur Laily; Suparno Suparno; Ngadiso Ngadiso (VELES Voices of English Language Education Society, 2023)
The perceptions of Indonesian EFL students on classroom-based assessment practices during the COVID-19 outbreak and the challenges they faced have received little attention. This phenomenon is the basis for why this research was conducted. To collect the data, questionnaires and interviews were applied to 20 senior high school students from grades eleventh and twelfth in Indonesia. Using a mixed-method design, this study declared that most students preferred classroom-based assessment during the COVID-19 outbreak, which was conducted online rather than traditional assessment before the outbreak. Classroom-based assessment practices during COVID-19 are considered more convenient and flexible, feel relaxed and less anxious, and improve their self-regulated learning. Moreover, Indonesian EFL students also revealed the challenges they faced in completing the assessment, such as internet network problems when the weather was terrible, the data package they used during the learning and assessment process being extravagant, and the lack of physical interaction with teachers and classmates. Further discussion about classroom-based assessment practices during the COVID-19 outbreak is necessary for more effective implementation and to positively affect EFL students and teachers.